PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA RIIL (Studi Empiris pada Perusahaan Subsektor Properti dan Real Estat yang Terdaftar di BEI pada Tahun 2019-2021) - Ramadhani, Risti Kurnia; Yuyetta, Etna Nur Afri (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of corporate governance on real earnings management. This study uses the proportion of independent commissioners, audit committee size, proportion of audit committees with accounting and financial expertise, frequency of audit committee meetings, size of the board of directors, managerial ownership, institutional ownership, and foreign ownership as independent variables and real earnings management as the dependent variable.            The population of this study is property and real estate subsector companies listed on the IDX in 2019-2021. The sample was determined using purposive sampling method and resulted in 43 companies that passed the criteria. The research hypothesis was tested using multiple linear regression analysis methods.             The test results show that the proportion of independent commissioners and the size of the board of directors have positive effect on real earnings management while the audit committee size, proportion of audit committees with accounting and financial expertise, frequency of audit committee meetings, managerial ownership, institutional ownership, and foreign ownership have no effect on real earnings management.